2022
DOI: 10.3389/fenvs.2022.985672
|View full text |Cite
|
Sign up to set email alerts
|

Niche and interspecific association with respect to the dominant phytoplankton species in different hydrological periods of Lake Wuchang, China

Abstract: In aquatic ecosystems, the dynamics of ecological parameters play an important role in community organizations. To understand the seasonal variation in the phytoplankton community in Lake Wuchang, Anhui Province, water samples were collected in three different hydrological periods (dry season, normal season, and wet season) from December 2019 to August 2020. The dominance value (Y), niche width (Bi), niche overlap (Oij), variance ratio method (VR), chi-squared test (χ2), and association coefficients were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…When the rapeseed reached the mature stage, plant and soil samples were collected from each cultivar. Most of the leaves of the rapeseed fell off during maturity under field conditions and, in our previous research, we found that the concentrations of Cd and Pb in the stems and leaves of rapeseed were similar [19,20]. Therefore, the remaining leaves were added to the stem for detection and analysis in this study.…”
Section: Sample Analysismentioning
confidence: 84%
“…When the rapeseed reached the mature stage, plant and soil samples were collected from each cultivar. Most of the leaves of the rapeseed fell off during maturity under field conditions and, in our previous research, we found that the concentrations of Cd and Pb in the stems and leaves of rapeseed were similar [19,20]. Therefore, the remaining leaves were added to the stem for detection and analysis in this study.…”
Section: Sample Analysismentioning
confidence: 84%
“…In the past years, its ecological environment used to be one of the best among lakes at the middle-lower reaches of the Yangtze River. However, due to climate change, industrial and agricultural production, and other human activities, the lake ecosystem has undergone great changes in recent years, and there is a risk of cyanobacterial blooms in summer when the weather is warm and rainy (Meng et al, 2022). Therefore, Lake Wuchang may exemplify the ecological and environmental changes of the whole Anqing Lake subregion under climate and human stressors.…”
Section: Introductionmentioning
confidence: 99%